2017
DOI: 10.3892/ol.2017.6701
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of sonic hedgehog signaling decreases viability and induces apoptosis in retinoblastoma cells: The key role of the PI3K/Akt pathway

Abstract: Retinoblastoma (RB) is the most common type of malignant intraocular cancer in teenagers. One of the proteins abnormally expressed during oncogenesis of RB is sonic hedgehog (SHH), which possesses the capability to selectively activate transcription factors of different genes. However, the detailed function of SHH in RB remains unknown. Thus, the present study sought to investigate the role of SHH in the development of RB. The human RB WERI-Rb-1 cell line was used as an in vitro model for the knockdown of SHH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The PI3K/mTOR signaling pathway is closely related to SHH (31). Studies have indicated that the PI3K/mTOR signaling has a synergistic effect on SHH signaling in embryonic development and cancer (21,31). To further investigate the relationship between the PI3K/mTOR and SHH pathways in liver cancer, the results in the present study clearly revealed that combined use of SHH and HDAC inhibitors blocked the activation of the PI3K/mTOR pathway and played an antitumor role.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The PI3K/mTOR signaling pathway is closely related to SHH (31). Studies have indicated that the PI3K/mTOR signaling has a synergistic effect on SHH signaling in embryonic development and cancer (21,31). To further investigate the relationship between the PI3K/mTOR and SHH pathways in liver cancer, the results in the present study clearly revealed that combined use of SHH and HDAC inhibitors blocked the activation of the PI3K/mTOR pathway and played an antitumor role.…”
Section: Discussionsupporting
confidence: 50%
“…It has been reported that inhibition of SHH signaling regulated pancreatic tumorigenesis via inhibition of the PI3K/AKT signaling pathway (21). Thus, it was investigated whether the dual inhibition of the SHH pathway and HDAC inhibited the growth of liver cancer cells via inhibition of the PI3K/AKT signaling pathway.…”
Section: Combined Use Of Vismodegib and Entinostat Synergistically Inmentioning
confidence: 99%
“…In the current study, Y79 and Weri-Rb-1 cells were utilized. However, these cell lines are in suspension and are thus difficult to use for the assessment of cell migration and invasion (6,28). For this reason, the current study only assessed cell proliferation and stemness, which serves as a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bai et al (11) revealed that miR-125b promotes tumor growth and suppresses apoptosis by targeting DNA Damage Regulated Autophagy Modulator 2 in RB. SHH signaling is another major pathway that is dysregulated in RB (6,25). SHH, a vertebrate homologue of the Drosophila segment polarity gene product, hedgehog, is associated with retina cell proliferation and differentiation during the process of embryonic development (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation